2013
DOI: 10.1021/om4000743
|View full text |Cite
|
Sign up to set email alerts
|

A Bis(phosphaethenyl)pyridine Complex of Iridium(I): Synthesis and Catalytic Application to N-Alkylation of Amines with Alcohols

Abstract: The iridium(I) complex [IrCl(BPEP-H)] (1), coordinated with 2,6-bis[2-(2,4,6-tri-tert-butylphenyl)-2-phosphaethenyl]pyridine (BPEP-H) as a PNP-pincer-type phosphaalkene ligand, has been synthesized and fully characterized by elemental analysis, NMR spectroscopy, and X-ray diffraction analysis. Complex 1 (1 mol %) catalyzes N-alkylation of primary and secondary amines with alcohols, leading to the selective formation of secondary and tertiary amines, respectively. Primary amines are smoothly alkylated with a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 100 publications
1
28
0
1
Order By: Relevance
“…N‐ Benzyl‐2‐phenethylamine (4a): 13 1 H NMR (300 MHz, CDCl 3 ): δ=7.31–7.15 (m, 10 H), 3.78 (s, 2 H), 2.90–2.86 (m, 2 H), 2.83–2.78 (m, 2 H), 1.53 (s, 1 H).…”
Section: Methodsmentioning
confidence: 99%
“…N‐ Benzyl‐2‐phenethylamine (4a): 13 1 H NMR (300 MHz, CDCl 3 ): δ=7.31–7.15 (m, 10 H), 3.78 (s, 2 H), 2.90–2.86 (m, 2 H), 2.83–2.78 (m, 2 H), 1.53 (s, 1 H).…”
Section: Methodsmentioning
confidence: 99%
“…2004 年, Ozawa 等 [68] 报道了该催化剂 下, 烯丙基醚的选择性去烯丙基化的反应(Scheme 31, D). 图式 31 二亚膦基环丁烯化合物在催化反应的应用 Scheme 31 Application of diphosphinidenecyclobutenes as catalyst 2013 年, Ozawa 课题组 [69] 报道了 1,6-二磷杂乙烯基 吡啶与铱的三齿络合物 49 催化一级氨和二级氨与醇的 N-烷基化反应, 产率高达 90%以上(Scheme 32).…”
Section: 膦烯化合物的性质unclassified
“…Though the alkylation of amines with alcohol has been of considerable interest in recent times with several studies reported with well‐defined molecular catalysts of Ir,40 Ru41 and Au42 in presence of an external base, or for that matter even under the in‐situ generated Ligand Assisted Catalysis conditions,43 the examples of truly bifunctional catalysts that perform without the requirement of an external base are only few in number (Figure 5). Extensive computational studies have also been undertaken on the “hydrogen borrowing” mechanism displayed by many of the catalysts described above 44…”
Section: 4 Alkylation Of Amines With Alcoholsmentioning
confidence: 99%